Mechanical Properties of Repair Welding High Yield Strength Structural Steel S690Q: SIFAT MEKANIK SAMBUNGAN LAS HASIL REPAIR BAJA STRUKTUR HIGH YIELD STRENGTH S690Q - Hendri Budi Kurniyanto; Diki Hadi Pratama; Imam Khoirul; M. Thoriq Wahyudi; Mukhlis (UIR PRESS, 2022)
Repeated welding caused by welding defects in the weld joint will result in changes in the mechanical properties of the weld joint, especially in the Heat Affected Zone (HAZ). Significant changes will occur when welding on steel materials that have undergone special treatment during the manufacturing process, such as quenched and tempered S690Q steel. S690Q steel is a structural steel with high yield strength with quenched and tempered conditions. The research was conducted by doing repeated welding as a simulation of the repair process using the GMAW process. Macro observations as well as tensile, bending, hardness, toughness tests were carried out on cross sections of welded joints. From the results of all the tests carried out the results meet the requirements of the BS EN ISO 15614-1 standard, but the results of the hardness test can identify significant changes in mechanical properties in the HAZ, especially in the bottom or root pass and hot pass areas. The average hardness value decreased from 334.07 HV at the top (face) to 209.55 HV and 198.88 HV at the bottom (hot pass and root pass) on the left side of the HAZ. While on the right side of the HAZ, the hardness value is 337.40 HV to 254.34 HV and 208.64 HV. Keywords: HAZ, S690Q, Structural Steel, Quenched and Tempered Steel